2019
DOI: 10.21776/ub.ruas.2019.017.01.2
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Penentu Preferensi Tipe Hunian di Kalangan Mahasiswa

Abstract: The universities development in Indonesia has implications on the increasing number of students. The tendency of the students majority who are transmigrants in the relevant college areas has further implications on the increasing need of shelter. Different backgrounds made different needs. Thus, there are several types of dwellings with their own characteristics. This study divides the dwellings into seven types, namely parents’ house, relatives’ house, bought house, apartment, unit rented house, rented house … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Research by Reski & Tampubolon [8] revealed that there were 14 reasons for preference for the type of housing among students, namely independence, atmosphere, comfort, accessibility, social interaction, financing, freedom, ownership, information, maintenance, privacy, demands, private facilities, and housing condition. Another study by Hajar & Susilawati [9] study shows that seven factors influence student decisions in choosing boarding houses.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Reski & Tampubolon [8] revealed that there were 14 reasons for preference for the type of housing among students, namely independence, atmosphere, comfort, accessibility, social interaction, financing, freedom, ownership, information, maintenance, privacy, demands, private facilities, and housing condition. Another study by Hajar & Susilawati [9] study shows that seven factors influence student decisions in choosing boarding houses.…”
Section: Introductionmentioning
confidence: 99%